Rating of perceived exertion in cycle ergometer: effect of maximal capacity difference - KURTEL, HIZIR; KASIMAY ÇAKIR, ÖZGÜR (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2012)
Aim: The purpose of this study was to evaluate cardiopulmonary responses of individuals with different fitness levels according to predetermined rating of perceived exertion (RPE) scores and to investigate the correspondence between the heart rate reserve percentage (HRR%) and the RPE scale by using fit and unfit subjects. Materials and methods: RPE scores of sedentary volunteers were recorded at different HRR% levels during graded exercise tests on a cycle ergometer. Following the tests, subjects were divided into 2 groups, high metabolic equivalent [(MET) MET >=. 10; n = 9] and low MET (MET < 10; n = 11), according to maximal O-2 uptakes (VO2max). Participants performed the steady-state exercise test at the 13th-14th level of their perceived exertion 48 h after the first test. Variance and regression analyses were performed. Results: For all HRR% values, RPE levels were not different between groups. During the graded exercise test, perceived exertion was significantly higher in the low MET group than in the high MET group. Predetermined RPE score results were significantly greater in the low MET group with relative O-2 consumption as compared to the high MET group (P < 0.05-0.001). Conclusion: In individuals with different VO2max levels, exercise intensity can be prescribed using HRR% or RPE scale methods while adjusting for individual differences in oxygen consumption.
Keywords: RPE scale; bicycle; VO2max differences; HEART-RATE; EXERCISE TEST; THRESHOLD; PRESCRIPTION; PARTICIPANTS; PREDICTION; INTENSITY; FITNESS; WOMEN